Cellulose acetate from palm oil bunch waste for forward osmosis membrane in desalination of brackish water - Saiful; Sharmila Hasima; Nurul Kamila; Rahmi (Results in Engineering, 2022)
Hygienic drinking water availability has become a significant problem in many parts of the world in emerging countries, developing countries, and the countries that often experience disasters, including Indonesia. Forward osmosis (FO) membrane is an alternative water treatment method, particularly in emergency water supplies. This study has developed a FO membrane for desalination brackish water to produce energy drinking water. The FO membrane was made from cellulose acetate (CA) polymer synthesized from cellulose isolated from waste palm oil empty fruit bunches (POEFB). The forward osmosis membranes were made by printing a polymer solution on a glass plate, followed by solidification and membrane formation. FT-IR spectrum confirmed the successful synthesis of cellulose acetate. The obtaining cellulose acetate showed that the cellulose produced was cellulose diacetate, with acetyl content and degree substitution, 36.17% and 2.15, respectively. The Cellulose diacetate FO membrane has a water flux value of 2.2 L/m2hour and a rejection factor of 96% using 1 M sucrose as a draw solution. The water quality of the FO product has met drinking water standards based on the regulation of the Minister of Health of the Republic Indonesia Number 492/MENKES/PER/VI/2010 and WHO standard drinking water quality.